A survey on the safety of the SARS-CoV-2 vaccine among a population with stroke risk in China - Wu, Gang; Zhang, Meixian; Xie, Xiaomei; Zhu, Yanwu; Tang, Hongxia; Zhu, Xinmiao; Liang, Yifan; Chen, Tao; Zhu, Kuangyao; Zhang, Danfeng; Jiang, Sujun; Jiang, Zhengli; et al. (Frontiers in Medicine, 2022)
Background: The safety of the COVID-19 vaccine in patients at stroke risk is poorly understood. Methods: A survey was conducted on risk factors related to stroke and adverse reactions to vaccines. The participants were divided into low-, medium-, and high-risk groups, according to the stroke risk scorecard recommended by the Stroke Prevention and Control Engineering Committee of the National Health and Family Planning Commission. Factors associated with adverse reactions were analyzed. Reasons for non-vaccination and the aggravation of underlying diseases after vaccination were investigated. Results: 1747 participants participated (138 unvaccinated). 36.8, 22.1, 41.1% of the vaccinated participants had low, medium, high risk of stroke, respectively. The incidence of adverse reactions after the first and second injection was 16.6, 13.7%, respectively. There was no difference in the incidence of adverse reactions among different risk groups. Sex, vaccine type, sleep quality, worry of adverse reactions, age, and education level were significantly related to adverse reactions to vaccination. The most popular reason for non-vaccination for medium- or high risk-participants was the aggravation of the existing disease. Only 0.3% of vaccinated participants reported slight changes in blood pressure, sugar levels, and lipid levels. No aggravation of stroke sequelae, atrial fibrillation, or transient ischemic attack was reported. Conclusions: Vaccination against COVID-19 (inactive virus) is relatively safe for people at risk of stroke. It is suggested to strengthen vaccine knowledge and ensure good sleep before vaccination.